Symptomatic giant coronary artery aneurysm treated with covered stents. Issue 7 (November 2020) - Della Rosa, Francesco; Molina-Martin de Nicolas, Javier; Bonfils, Laurent; Fajadet, Jean
Abstract : Supplemental Digital Content is available in the text.